Post-Covid-19 Pandemic Awareness on The Use of Micro- and Nano Plastic and Efforts into Their Degradation - A Mini Review - Ekwan Nofa Wiratno; Amira Azawani Mohd Rozdhl; Nafizatun Eliana Ali Hanafi; Rabiatul Alia Redzuan; Fahrul Zaman Huyop (Journal of Tropical Life Science, 2021)
Micro- and nanoplastic pollution possess a global threat and cause a future problem and needs greater attention. Its pollution is also exacerbated recently by the use of abundance of plastic polymers in efforts to prevent and handle COVID-19 pandemic at the global scale. This review covered the major concerns about the characteristic, effect and bioremediation of micro- and nanoplastics of post COVID-19. Based on size, microplastic is described as debris particles smaller than 5 mm whereas, nanoplastic is referred to any particles smaller than 100 nm. Micro- and nanoplastic are easily ingested by many aquatic organisms at different trophic levels. This ingestion caused negative health impacts to all living organisms. Microplastic direct effect on living organism for example mechanical injury, false satiation, declined growth, promoted immune response, energy loss, disrupted enzyme activity and production, decreased fecundity, production of oxidative stress, and mortality. Nanoplastic could enter the circulatory system and caused negative effects on the cellular and molecular levels. Bioremediation of microplastic by magnoliophyta, bacteria, fungus and algae on several polymer forms was previously reported, however, not many on nanoplastic biodegradation. Therefore, current review will focus on the characteristics, effect and bioremediation effort of micro- and nanoplastic.